Socioeconomic inequalities in the prevalence of chronic diseases and preventive care among adults aged 45 and older in Shaanxi Province, China - Sha Lai; Chi Shen; Xiaowei Yang; Xiaolong Zhang; Yongjian Xu; Qian Li; Jianmin Gao; Zhongliang Zhou (BMC, 2019)
Abstract Background Monitoring inequalities in chronic disease prevalence and their preventive care can help build effective strategies to improve health equality. Using hypertension and diabetes as a model, this study measures and decomposes socioeconomic inequalities in their prevalence and preventive care among Chinese adults aged 45 years and older in Shaanxi Province, an underdeveloped western region of China. Methods Data of 27,728 respondents aged 45 years and older who participated in the fifth National Health Services Survey conducted in 2013 in Shaanxi Province were analyzed. The relative indexes of inequalities based on Poisson regressions were used to assess disparities in the prevalence of hypertension and diabetes and their preventive care between those with the lowest and the highest socioeconomic status, and the concentration index was used to measure the magnitude of the socioeconomic-related inequality across the entire socioeconomic spectrum. The contribution of each factor to the inequality was further estimated via the concentration index decomposition. Results Our results indicate a higher prevalence of hypertension and diabetes among the rich than the poor individuals aged 45 years and older in Shaanxi Province, China. Among individuals with hypertension or diabetes, significant inequalities favoring the rich were observed in the use of preventive care, i.e. in adequate use of medication and of blood pressure/blood glucose monitoring. Furthermore, economic status, educational level, employment status, and urban-rural areas were identified as the key socioeconomic indicators for monitoring the inequalities in the patient preventive care. Conclusions Our study suggests that the existence of clear inequities in the prevalence of chronic diseases and preventive care among adults aged 45 and older in Shaanxi Province, China. These inequalities in chronic diseases could be as much a cause as a consequence of socioeconomic inequalities.